2011
DOI: 10.1088/0964-1726/20/3/035018
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological model for pre-stressed piezoelectric ceramic stack actuators

Abstract: In order to characterize the hysteretic characteristics between the output displacement and applied voltage of pre-stressed piezoelectric ceramic stack actuators (PCSAs), this paper considers that a linear force and a hysteretic force will be generated by a linear extension and a hysteretic extension, respectively, due to the applied voltage to a pre-stressed PCSA and the total force will result in the forced vibration of the single-degree-of-freedom (DOF) system composed of the mass of the pre-stressed PCSA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…where and are the equivalent damping and stiffness of PSAs, respectively, and can be obtained by the identification method proposed in [20]. Equations ( 1)-( 3) and ( 6) define the simplified comprehensive model for PSAs.…”
Section: Modified Comprehensive Model For Psasmentioning
confidence: 99%
See 1 more Smart Citation
“…where and are the equivalent damping and stiffness of PSAs, respectively, and can be obtained by the identification method proposed in [20]. Equations ( 1)-( 3) and ( 6) define the simplified comprehensive model for PSAs.…”
Section: Modified Comprehensive Model For Psasmentioning
confidence: 99%
“…However, the current literatures indicated that the existing researches are mainly focused on hysteresis models for PSAs, such as the Preisach model [4][5][6][7], the Prandtl-Ishlinskii model [8,9], the Polynomial model [10,11], the Neural Network model [12,13], the Maxwell model [14,15], the Duhem model [16], the LuGre model [17,18], the differential model [19], and the Bouc-Wen model [19][20][21]. These hysteresis models for PSAs can only simulate the hysteresis characteristics of PSAs.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the hysteresis modeling approaches include Preisach model [11], Prandtl-Ishlinskii (PI) model [12][13][14], and Bouc-Wen model [15].…”
Section: Introductionmentioning
confidence: 99%
“…16 Non-linear hysteresis, creep and saturation effects are inherent characteristics of the piezoelectric actuator, which can negatively affect its performance. Numerous hysteresis models have been developed, which include the Prandtl-Ishlinski, 17,18 Preisach, 19,20 Bouc-Wen 21 and quadratic hysteresis models. 22,23 The hysteresis characteristic can be mitigated using their inverse model, which linearize the hysteresis of the piezoelectric actuator, but most of the time, without taking the saturation effect into consideration.…”
Section: Introductionmentioning
confidence: 99%